Sexually Transmitted and Blood-borne Infections Among Patients Presenting to a Low-barrier Substance Use Disorder Medication Clinic. Issue 6 (November 2021) - Harvey, Leah; Taylor, Jessica L.; Assoumou, Sabrina A.; Kehoe, Jessica; Schechter-Perkins, Elissa M.; Bernstein, Edward; Walley, Alexander Y.
Abstract : Objective: To study the infection-related needs of patients with substance use disorders initiating care at a low-barrier-to-access program (LBAP) by describing the proportion with human immunodeficiency virus (HIV), hepatitis B and C virus (HBV, HCV), syphilis, gonorrhea, and chlamydia and determining rates of treatment and/or linkage to care. Methods: We reviewed the records of patients who completed an intake visit at an LBAP in Boston, MA during the first 9 months after implementation of a standardized intake laboratory panel (January 30, 2017–September 30, 2017). Results: Among 393 patients initiating care, 84.7% (n = 333) completed at least 1 screening test. Baseline rates of HIV (9/393, 2.3%), current or past HCV (151/393, 38.4%), and chronic HBV (2/393, 0.5%) were high. Sixty-one new, active infections were identified through screening, including 1 HIV, 3 syphilis, 4 gonorrhea, 3 chlamydia, 1 chronic, and 1 acute HBV, and 48 cases of viremic HCV. Many patients were nonimmune to HBV (102/270, 37.8%) and HAV (112/255, 43.9%). Among new diagnoses, treatment was documented in 88% of bacterial infections and linkage occurred in 0/1 HIV, 2/2 HBV (100.0%), and 16/48 HCV (33.3%) cases. Conclusions: Patients initiating SUD care at an LBAP have substantial, unmet infection-related needs. Results justify the inclusion of comprehensive infection prevention, screening, and linkage-to-treatment protocols in LBAPs.